DMSO and its role in differentiation impact efficacy of human adenovirus (HAdV) infection in HepaRG cells - Hofmann, Katharina; Hofmann, Samuel; Weigl, Franziska; Mai, Julia; Schreiner, Sabrina (Viruses, 2024)
Differentiated HepaRG cells are popular in vitro cell models for hepatotoxicity studies. Their differentiation is usually supported by the addition of dimethyl sulfoxide (DMSO), an amphipathic solvent widely used in biomedicine, for example, in potential novel therapeutic drugs and cryopreservation of oocytes. Recent studies have demonstrated drastic effects, especially on epigenetics and extracellular matrix composition, induced by DMSO, making its postulated inert character doubtful. In this work, the influence of DMSO and DMSO-mediated modulation of differentiation on human adenovirus (HAdV) infection of HepaRG cells was investigated. We observed an increase in infectivity of HepaRG cells by HAdVs in the presence of 1% DMSO. However, this effect was dependent on the type of medium used for cell cultivation, as cells in William’s E medium showed significantly stronger effects compared with those cultivated in DMEM. Using different DMSO concentrations, we proved that the impact of DMSO on infectability was dose-dependent. Infection of cells with a replication-deficient HAdV type demonstrated that the mode of action of DMSO was based on viral entry rather than on viral replication. Taken together, these results highlight the strong influence of the used cell-culture medium on the performed experiments as well as the impact of DMSO on infectivity of HepaRG cells by HAdVs. As this solvent is widely used in cell culture, those effects must be considered, especially in screening of new antiviral compounds.